PENGARUH HERBAFARM DAN PUPUK NPK MUTIARA 16:16:16 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vignaradiata L.) - Rahmayani Pulungan; Maizar; M. Nur (UIR Press, 2018)
ABSTRACT The purpose of this study was to determine the interaction and main effects of herbafarm and NPK Mutiara 16:16:16 fertilizer on the growth and production of mung bean plants. (H) consisting of 4 levels namely 0, 1.5, 3, 4.5 cc / L of water, and the second factor is NPK Mutiara 16:16:16 (N) consisting of 4 levels of treatment namely 0, 10.8, 21.6,32.4 grams/plot, so that there are 16 treatment combinations with 3 replications there are 48 experimental unit plots. Each experimental unit consisted of 12 plants and 2 of them were used as sample plants so that the entire plant was 576 plants. The best treatment was giving herbafarm 3 cc / l water and NPK fertilizer pearl 21.6 g / plot ((H2N2) with the results the best filling speed of dry matter is 0.33 g, the percentage of planted pods is 71.33%, the weight of dry seeds is 27.50 grams per harvest. The main effect of giving herbafarm 3 cc / l water gives the best results on plant height 65.67 cm, age flowering 31.92 days, effective filling time 19.74 days and weighing 100 seeds 5.99 grams, while applying NPK pearl fertilizer 21.6 g / plot gives the best results on plant height 61.67 cm and effective filling time 19.90 days, but the application of pearl NPK fertilizer 32.4 g / plot gave the best results at the age of flowering 32.26 days and weighing 100 seeds 5.96 grams. Keywords: Herbafarm, Growth, Production, Mung Beans.